essential oil profiling and antioxidant potential of two plant species - Bougoffa Manar; Ghalia Habiba; Lakehal Mounia (Université of Eloued, 2025)
This study investigates the chemical composition and antioxidant activity of essential oils extracted from two medicinal plants: Mentha piperita (peppermint) and Ammodaucus leucotrichus (desert cumin), both traditionally used in Algerian folk medicine. Essential oils were obtained by hydro distillation and analysed using Gas Chromatography–Mass Spectrometry (GC-MS), revealing the dominance of menthol and menthone in Mentha piperita, and cumin aldehyde and thymol derivatives in Ammodaucus leucotrichus. The antioxidant capacity of the oils was evaluated using both the DPPH radical scavenging assay and cyclic voltammetry. Results showed that Mentha piperita had a stronger radical scavenging activity, with an IC₅₀ of 49.0 µg/mL, while Ammodaucus leucotrichus exhibited an IC₅₀ of 59.1 µg/mL, both outperforming the standard α-tocopherol (IC₅₀ = 70.8 µg/mL). Electrochemical analysis confirmed the electron-donating ability of the oils, further supporting their antioxidant potential. These findings validate the traditional use of both species and highlight their potential as natural sources of bioactive compounds for pharmaceutical and nutraceutical applications. Further studies are recommended to evaluate their broader biological effects and ensure safety for therapeutic use.
Keywords: Mentha piperita; Ammodaucus leucotrichus; Essential Oils; GC-MS; DPPH; Antioxidants Activity; Cyclic Voltammetry